Dyslipidemia testing: Why, for whom and when. Issue 4 (August 2015) - Galema-Boers, J.M.H.; van Lennep, J.E. Roeters
Highlights We examine the recommendations of lipid testing in the primary CVD prevention setting. Recommendations in whom to test lipids differ among the guidelines. The engagement of the patient as a partner in CVD prevention is required.